A general algorithm for flexible active power control of photovoltaic systems - Dehghani Tafti, Hossein (2018)
The maximum power point tracking (MPPT) is generally implemented in grid-connected photovoltaic (PV) power plants to maximize the energy yield. However, as the penetration level increases, challenging issues such as overloading and overvoltage arise in PV applications. Accordingly, a constant power generation (CPG) operation, in which the PV output power is limited to a specific value, has been imposed by some grid regulators to alleviate the integration challenges. In that case, the combined operation of MPPT and CPG is required, which increases the complexity of the controller design. To generalize the two control objectives, a flexible active power control algorithm that combines both MPPT and CPG operating modes is proposed. The proposed algorithm can optimize the performance in both modes (i.e., MPPT and CPG). By adjusting the voltage-step between two consecutive operating points, fast dynamics and low-power oscillations can be obtained. The performance of the proposed strategy is evaluated through simulations and experiments under different irradiance and power reference profiles.